The motivation of secondary school principals to improve and sustain quality academic performance in Grade 12 - Valentin, A (North-West University (South Africa), 2019)
This qualitative research aimed to understand the influence of the motivational level of the secondary school principal on the academic performance of the Grade 12 learners. The Self- Determination and Expectancy Attribution theories were used. From the theories, the following factors influencing motivation were identified: trusting relationships, learning environment, participating in setting goals, feedback and self-motivation. Two performing schools and two underperforming schools were sampled. The principal of each school together with three educators from each school were interviewed to establish if the factors influencing motivation influenced the motivational level of the principal to move the educators to optimal performance. All data collected during the semi-structured interviews were transcribed and coded to extract the facts on the impact of the principal towards academic performance. The conclusion was made that the principal must have intrinsic motivation before any movement of the educators can take place towards better performance.
MEd (Management), North-West University, Potchefstroom Campus
Keywords: Motivational level; secondary school principals; academic performance; Grade 12